2018
DOI: 10.1016/j.clim.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib trial of folate binding protein (FBP)-derived peptide vaccines, E39 and an attenuated version, E39’: An analysis of safety and immune response

Abstract: NCT02019524.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Furthermore, OC patients with high FRα expression have reduced relapse-free survival (RFS) and overall survival (OS) rates relative to patients with low FRα expression 8 . Numerous other studies have validated FRα as a target antigen for diverse approaches to OC immunotherapy, including tumor vaccines, antibody treatment, and CAR-T cells [9][10][11][12][13][14][15][16][17][18][19] . We tested OC (and breast cancer) patients for spontaneous immune responses to putative HLA class II-binding epitopes and identified five FRαderived epitopes to which patients (but not healthy volunteers) exhibit an immune response 20 .…”
mentioning
confidence: 99%
“…Furthermore, OC patients with high FRα expression have reduced relapse-free survival (RFS) and overall survival (OS) rates relative to patients with low FRα expression 8 . Numerous other studies have validated FRα as a target antigen for diverse approaches to OC immunotherapy, including tumor vaccines, antibody treatment, and CAR-T cells [9][10][11][12][13][14][15][16][17][18][19] . We tested OC (and breast cancer) patients for spontaneous immune responses to putative HLA class II-binding epitopes and identified five FRαderived epitopes to which patients (but not healthy volunteers) exhibit an immune response 20 .…”
mentioning
confidence: 99%
“…The benefit of boosting in this trial must be interpreted with caution as only patients who remained disease‐free 12 months after enrollment received boosters, creating some inherent bias in the comparison to the control group. We have, however, shown the efficacy of boosting in previous trials, and will continue to incorporate booster inoculations into future studies . With respect to boosting with full strength or attenuated peptides, the current study serves to show the safety of this approach, but additional trials with higher power are needed to elucidate any differences.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast with this finding, however, there are concerns that repeated stimulation by a single immunogenic TAA may lead to increased tolerance and decreased immunologic memory over time . For this reason, we have developed an attenuated version of the E39 vaccine, E39′ (EIWTFSTKV, also known as J65), which has been shown in preclinical testing to induce effective FBP‐specific cytotoxicity and has shown efficacy when combined with E39 in an early clinical trial . Given concerns about repeated stimulation with the same peptide, and the promising preclinical work with E39′, we randomized patients in this trial to boosting with either E39 or E39′ to examine the long‐term immunologic effects…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also synthesized peptide 1412 (QPEQQETKKEEQ) and this peptide showed outstanding binding activity to most of the applied MHCs ( Mahdavi and Moreau, 2016 ). Peptide E39 (EIWTHSYKV) ( Vreeland et al, 2018 ) was combined with peptide E39’ (EIWTFSTKV), an attenuated version of E39. Immune analyses suggested that the optimal cytotoxic T lymphocyte population was induced by administering with E39 and E39’ in t urn.…”
Section: Peptide-based Cancer Vaccinesmentioning
confidence: 99%